The Dynamics of Work Communication of Event Organizers and Vendors as a Learning Process of Non-Formal Education in the Event Industry - Ristanto Sumarsono; Yudan Hermawan; A. Hasdiansyah (Educia Journal, 2026)
Work communication in the event industry is commonly understood as a mechanism for coordinating tasks, managing information flow, and ensuring successful event execution. However, its role as a process of non-formal learning and professional competence development remains insufficiently explored. This study aims to examine how communication between Event Organizers (EOs) and vendors functions as a learning mechanism within the event industry. A qualitative case study approach was employed at Matoa Corner Production, an event organizing and production company in Indonesia. Data were collected through semi-structured interviews, participatory observation, and document analysis involving 10 participants consisting of Event Organizers, vendors, and field crews. Data were analyzed using the interactive model of Miles, Huberman, and Saldaña, involving data condensation, data display, and conclusion verification. The findings reveal that work communication operates as a continuous non-formal learning process across three interconnected stages: pre-event communication, event implementation communication, and post-event evaluation. During the pre-event stage, communication facilitates shared understanding, knowledge exchange, and coordination among stakeholders. During event implementation, communication enables collaborative problem-solving, adaptive decision-making, and the development of practical competencies through real-time workplace experiences. Meanwhile, post-event communication supports reflection, knowledge consolidation, and continuous improvement of professional practices. The study demonstrates that communication in the event industry extends beyond operational coordination and serves as a strategic mechanism for workplace learning, knowledge transfer, and organizational capability development. This research contributes to management and workplace learning studies by highlighting communication as an essential organizational resource that supports professional development in dynamic project-based industries.